Tobacco TGA factors differ with respect to interaction with NPR1, activation potential and DNA-binding properties - Niggeweg, Ricarda; Thurow, Corinna; Weigel, Ralf; Pfitzner, Ursula; Gatz, Christiane (Plant molecular biology, 2000)
In higher plants, as-1-like cis elements mediate auxin- and salicylic acid-inducible transcription. Originally found in viral and T-DNA promoters, they are also functional elements of plant promoters activated during the defence response against pathogens. Tobacco bZIP transcription factor TGA1a was the first recombinant protein shown to bind to as-1. cDNAs for two novel tobacco as-1-binding bZIP proteins (TGA2.1 and TGA2.2) were isolated. Revealing a high degree of amino acid identity in the bZIP domain (89%) and the C-terminus (79%), the two TGA2 factors differ remarkably with respect to the length of the N-terminus (170 amino acids in TGA2.1 versus 43 amino acids in TGA2.2). TGA2.1 and TGA2.2, but not TGA1a, interacted with ankyrin repeat protein NPR1, a central activator of the plant defence response. In contrast, TGA2.1 and TGA1a, but not TGA2.2, functioned as transcriptional activators in yeast. Apart from conferring transcriptional activation, the N-terminal domain of TGA2.1 led to reduced in vitro as-1-binding activity and almost completely abolished binding to one half site of this bifunctional element. When being part of a heterodimer with TGA2.2, TGA2.1 was efficiently recruited to a single half site, though double occupancy of the element was still preferred. In contrast, TGA1a preferred to bind to only one palindrome, a feature that was also maintained in heterodimers between TGA1a and TGA2.1 or TGA2.2.